Prefix In Mongondow Language - Donald Matheos Ratu; Veronika Listi Ferdini Damopolii (English Education Department, 2023)
The goal of this research is to explain the word formation, prefix, of the Mongondow language. The method used in this study is a taxonomic descriptive method, namely exposure by classifying language elements according to hierarchical relationships. The results of the research show word formation patterns are done by adding prefixes, infixes, suffixes, confixes, and clitics. In this pattern of word formation, a morphophonemic process occurs, resulting in new forms like phoneme modifications or deletions. Reduplication and compounding procedures can also result in word formation patterns. As a result of forming words with these patterns a new class of words is formed. The focus of this research is to reveal the prefix in Mongondow Language. The result show there are Prefix moN-, mo-, no-,poN-, ko- ,mopo-, nopo-, popo-, moko-, noko-, poko-, mogi- , nogi-, pogi-, mojiN-, pongiN-, moki- poki-, moliN, noliN-, moi-, noi-, monoN-, nonoN-, mopoko-, nopoko-, mopopo-, mopoko, poro- , pinoro-, pinoro-, pino-, pinopo-, poR-, toR, kinoR- iand those prefixes depict process with root morphemes functions and form specific categorical word class",